Physical activity and bone turnover in women with osteopenia - Perić, Dušan; Kovačev-Zavišić, Branka; Medjedović, Bojan; Romanov, Romana; Ahmetović, Zlatko; Novaković-Paro, Jovanka; Dimitrić, Mirjana (Vojnosanitetski pregled, 2020)
Background/Aim. Osteoporosis is a systemic disease of the skeleton characterized by a decrease in bone mass and changes in the bone structure. An increased tendency of the bone tissue for fractures occurs as a consequence of these changes. The initial phase of physiological aging of the bones that gradually leads to osteoporosis is osteopenia. This paper tracks the effects of a specific kind of physical exercise program in women with osteopenia. The aim was to quantify the impact of this program on: the concentration of bone metabolism blood markers, muscle strength, aerobic capacity, and physical dimensions. Methods. The sample consisted of 26 women in postmenopause (age 46–58) divided into two groups – experimental group (n = 15) and control group (n = 11). A combined program of exercise consisting of aerobic activities and strength training was applied in the experimental group, while the control group did not join in the exercise program. The program lasted for 7 weeks, three times a week with a break day between the trainings. The intensity of the aerobic training was in the span of 60% to 70% of heart rate reserve (HRR), and the intensity of the strength training was in the span of 60% to 85% of one repetitive maximum (1RM). Osteopenia was diagnosed prior to the experiment by applying a dual energy X-ray absorptiometry of the lumbar spine and the hip. The following was measured before and after the experiment: the level of biochemical markers in the serum [Beta-aspartic acid β-cross laps (CTx), total procollagen type 1 N-terminal peptide (tP1NP) and bone isoenzyme of alkaline phosphatase (ALP), 1RM of leg extensors, maximum oxygen consumption (VO2 max), bodily height and mass, and a calculated Body Mass Index (BMI). Results. Significant changes were determined only in the experimental group. During the experimental period, there was a significant increase of muscle strength and VO2 max, with a decrease of Beta-CTx concentration. No statistically significant changes were recorded in the control group. Conclusion. A 7-week period of systematic exercise showed to be sufficient to increase muscle strength and VO2 max, partially also to decrease bone resorption, but insufficient to alter bone volume, bodily mass, and BMI.
Keywords: bone diseases, metabolic; osteoporosis, postmenopausal; exercise; densitometry; blood chemical analysis; muscle tonus; serbia.